Impact Of Foreign Currency Hedging On Firm Value Among Indian Corporates - Gupta, Amit (2016)
Indian economy was opened for globalization in 1991 and Indian Rupee was deregulated in 1993 and subjected to market fluctuations. Indian Rupee was very volatile during the past decade due to global events like US subprime crisis (2007-2009), European sovereign debt crisis, Oil prices fluctuations and Fed monetary policy speculations to name few. This volatility has put pressure on Indian firms to manage their foreign currency exposure. Hedging and use of Foreign Currency Derivatives (FCD) is the preferred way of hedging forex risk. This paper tries to find out how the use of hedging impacts Indian firms value. Data for 129 top Indian non-financial companies for the period of 2008 to 2014 is collected from their annual reports and Datastream database. Approximately 800 annual reports were analyzed to get derivative and foreign currency use data of these firms. Univariate and multivariate analysis is carried out to check impact of hedging on firm’s value in different settings. Control variables are used in multivariate analysis to check effect of other parameters on firm’s value. OLS regression finds that hedging has positive impact on firms’ value. This result is robust if samples are divided based on foreign sales or asset wise. Analysis done for financial crisis period (2007-2009) also shows positive effect of hedging with analysis done on post crisis period (2010-2014) which also shows value creation by hedging. Findings show that notional value of derivatives is not statistically significant for firm’s value. This is explained by the fact that firm’s disclosures of derivatives in annual reports are not uniform. Some firms do not disclose notional value of derivatives clearly. This also highlights the need of clear regulation for derivative declaration in annual reports. Study recommended adopting new accounting standards as soon as possible. This will help investors to make better informed decisions. It is also recommended to make it mandatory to hedge partially a portion of foreign currency debt.